STUDI LITERATUR : PENDIDIKAN KARAKTER DALAM MEMBANGUN ETIKA MORAL SISWA DI SEKOLAH DASAR - Nofeni Ramadani; Chindika Parinci Utami; M. Rivaldi; Akhmad Faisal Hidayat (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
Character education in elementary schools has a very important role in forming students' moral ethics. Values ​​such as honesty, responsibility, empathy and discipline are taught to guide students in interacting with the social environment. This article aims to analyze how character education can be applied in building students' moral ethics in elementary schools, as well as the role of teachers and parents in this process. This research uses a literature review method, by examining various related literature sources that discuss the application of character education, both in the curriculum, extracurricular activities, and in daily life at school. The results of this study show that a consistent and collaborative approach between schools and families can strengthen student character formation. Effective character education does not only focus on teaching moral values, but also on forming students' ethical attitudes and behavior in their social life.